Prenatal experience with language shapes the brain - Benedetta Mariani; Giorgio Nicoletti; Giacomo Barzon; María Clemencia Ortíz Barajas; Mohinish Shukla; Ramón Guevara; Samir Suweis; Judit Gervain (2023)
Human infants acquire language with notable ease compared to adults, but the neural basis of their remarkable brain plasticity for language remains little understood. Applying a scaling analysis of neural oscillations to address this question, we show that newborns' electrophysiological activity exhibits increased long-range temporal correlations after stimulation with speech, particularly in the prenatally heard language, indicating the early emergence of brain specialization for the native language.